2014
DOI: 10.1128/jvi.03445-13
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of T Cell Responses during Active Varicella-Zoster Virus Reactivation in Human Ganglia

Abstract: Varicella-zoster virus (VZV) is responsible for both varicella (chickenpox) and herpes zoster (shingles). During varicella, the virus establishes latency within the sensory ganglia and can reactivate to cause herpes zoster, but the immune responses that occur in ganglia during herpes zoster have not previously been defined. We examined ganglia obtained from individuals who, at the time of death, had active herpes zoster. Ganglia innervating the site of the cutaneous herpes zoster rash showed evidence of necros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 45 publications
5
81
1
2
Order By: Relevance
“…14,[26][27][28][29] In our study, the observation that vaccine efficacy was maintained even among patients in the oldest age group, in conjunction with previous clinical data showing that HZ/su immunogenicity decreases only minimally with increasing age, suggests that HZ/su can overcome immunosenescence to provide protection against herpes zoster. 19,21,30-32 The immune response to HZ/su in both older persons and those with immunosuppression that was observed in earlier clinical studies might be attributed to the AS01 B adjuvant system, which boosts VZV-specific memory immune responses.…”
Section: Discussionsupporting
confidence: 67%
“…14,[26][27][28][29] In our study, the observation that vaccine efficacy was maintained even among patients in the oldest age group, in conjunction with previous clinical data showing that HZ/su immunogenicity decreases only minimally with increasing age, suggests that HZ/su can overcome immunosenescence to provide protection against herpes zoster. 19,21,30-32 The immune response to HZ/su in both older persons and those with immunosuppression that was observed in earlier clinical studies might be attributed to the AS01 B adjuvant system, which boosts VZV-specific memory immune responses.…”
Section: Discussionsupporting
confidence: 67%
“…This is in agreement with the immune mechanism that controls other herpesviral infections (27, 28) and with previous reports showing that adults with recent and/or frequent exposures to VZV, who did not develop symptomatic VZV infection, had robust VZV-specific CD8+ and CD4+ T cell responses detected by ex vivo restimulation (2931). The important role of CD8+ T cells in the control of VZV replication could also be inferred from the accumulation of this T cell subset in the ganglia of individuals with HZ, where VZV is actively replicating (32). Furthermore, we showed that high frequencies of VZV-specific CD8+ CTL detected by ex vivo restimulation in HIV-infected children correlated with protection against HZ (33).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies report the presence of T cells (primarily noncytolytic CD8 ϩ T cells), B cells, macrophages, and natural killer cells within ganglia isolated from individuals who suffered from herpes zoster shortly before they died from other causes (7)(8)(9). These studies also showed increased expression of chemokine CXCL10, which binds to CXCR3 to induce migration of memory T cells and natural killer cells (8), as well as increased expression of major histocompatibility complex class I (MHC-I) and MHC-II molecules (9). These observations suggest that both innate and adaptive immunity play a critical role in the resolution of VZV reactivation.…”
mentioning
confidence: 99%